Comparison of sympathomimetic effectiveness in children with congenital heart diseases after cardiopulmonary bypass surgery - Khemio Arnes, S.; Moshkivska, L.; Teslar, M.; Cheburahin, V.; Boyko, S.; Lazoryshynetz, V. (Ukrainian Journal of Cardiovascular Surgery, 2016)
The current work evaluates the application of sympathomimetic drugs in infants with congenital heart diseases after cardiopulmonary bypass surgery. The comparison between adrenaline and dopamine in the treatment of postoperative myocardial dysfunction, the frequency of postoperative complications and the length of stay in the intensive care unit was accomplished.